(untitled) (Tzintzun, Revista de Estudios Históricos, 2021)
The goal of this work is to show how from 1955 on, during the General Francisco Franco’s dictatorship, the children of professional military men enjoyed cultural, educational and sanitary conditions that were out of reach for the rest of the infant population. Among other benefits, there were children school colonies, which were supposed to be a tool for social and academic promotion that emphasized social differences.